Holistic integrative medicine declaration (KeAi Communications Co., Ltd., 2024)
Holistic integrative medicine, abbreviated as HIM, has been officially proposed since 2012. Its theoretical system has been continuously improved, and its practical methods have become increasingly diverse, becoming an inevitable choice and path for the medical development in the new era. This article demonstrates ten major propositions for HIM, elaborating on the connotation and extension of HIM from the perspectives of epistemology and methodology, in order to achieve the transformation and adaptive evolution of modern medicine.